Detection of 3,4-dichloroaniline in different matrices using chemically modified glassy carbon electrode - Wong, Ademar [UNESP]; Santos, Anderson M.; Cárdenas-Riojas, Andy A.; Calderon-Zavaleta, Sandy L.; Feitosa, Maria H.A.; Moraes, Fernando C.; Baena-Moncada, Angélica M.; Sotomayor, Maria D.P.T. [UNESP] (Elsevier, 2024)
The present work reports the development and application of a new electrochemical sensor for the detection of the diuron metabolite 3,4-dichloroaniline (3,4-DCA); the sensor was developed using a glassy carbon electrode (GCE) based on carbon nanofibers modified with silver nanoparticles and poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS film). Voltammetric measurements were performed using phosphate buffer solution as electrolyte, where well-defined current responses were obtained upon the addition of increasing concentrations of 3,4-DCA. The application of the proposed sensing device yielded the following results: concentration range of 1.0 × 10−7 to 1.0 × 10−5 mol/L; sensitivity of 0.39 µA µmol/L; and detection limit of 5.0 × 10−8 mol/L. The proposed sensor was successfully employed for the detection of 3,4-DCA in the presence of other pesticides and interfering compounds without any significant interference from these species. Finally, the sensing device was applied in soil, sewage, tap water, and river water samples using the spiking method; the results obtained showed recovery percentages ranging from 92 to 108 %. These findings point to the reliability and efficiency of the proposed method when applied for 3,4-DCA detection.